Shadow Detection: A Review of Various Approaches to Enhance Image Quality - Vincent, Noel; Mathew, Shiny (International Journal of Computer Sciences and Engineering, 2014)
Shadow Elimination is the removal of shadow without disturbing the quality of the image from either indoor and outdoor scenes or any other scenes. This review covers up all the different techniques and algorithms used in shadow elimination process as well as gives a brief description of the advantage and disadvantage of each algorithm used; therefore making an easy platform for the researchers to work more precisely with image processing to yield better growth in science and technology especially in geostatistic.